Disruptions of Covid-19 pandemic on English literacy - Ina Suryani, Ab Rahim; Nazifah, Hamidun; Nor Hanim, Awang @ Mohd Noor; Noazli, Abu Bakar; Mariam, Idris; Nor Khairi, Ahmad (Universiti Malaysia Perlis, 2024)
Illiteracy, which is the inability to read and write, can limit individuals' opportunities, reduce their quality of life, societies, and economies. Given the recent pandemic, movement control order was enforced at various phases due to COVID-19 and impacted learning due to school closures. This study aims to identify the impact of COVID-19 on English Literacy Among Primary School Students. A total of 800 students from 46 primary schools participated in this study. The students were selected based on the teachers’ class observation and reading evaluation. A literacy test consisting of six literacy skill was conducted individually by language teachers. Findings on literacy skills one to level six revealed that literacy skill two to six are alarming, suggesting illiteracy is rising. In conclusion, intervention is direly needed to uphold the good literacy record. The implication of the study is to warn on the rising of illiteracy at alarming rate due to Covid-19 quarantine. Further research is recommended to other population in describing how the pandemic has affected English literacy in different regions and countries.